Feeling coerced during psychiatric hospitalization: Impact of perceived status of admission and perceived usefulness of hospitalization. (November 2019) - Golay, Philippe; Morandi, Stéphane; Silva, Benedetta; Devas, Célia; Bonsack, Charles
Abstract: Introduction: Perceived coercion is not exclusively related to the patient's legal status at admission. Patients are not always aware of their correct status and voluntary patients often report having felt coerced. Moreover, involuntary patients commonly report that their hospitalization was justified. The first goal was to disentangle the contribution of the legal and of the perceived status of admission in predicting perceived coercion. The second goal of this study was to investigate to which extent perception of the usefulness of the hospitalization affected perceived coercion. Material and methods: 152 inpatients were interviewed about their knowledge of their legal status of admission, perceived need for hospitalization and subjective improvement. They completed the MacArthur's Admission Experience Survey and the Coercion Experience Scale. Results: 6.6% of voluntarily admitted patients and 30.4% of involuntarily admitted patients reported an erroneous status of admission. 88.2% of voluntarily admitted patients and 44.7% of involuntarily admitted patients felt that they needed hospitalization during their stay. Levels of perceived coercion at admission and during hospitalization were mostly predicted by their perceived legal status. While involuntary patients frequently perceived the need for hospitalization and reported subjective improvement after admission, their perception of coercion markedly differed from voluntary patients. Conclusions: Perceived coercion was marginally related to the legal admission status, which leaves room for interventions that reduce the patients' feeling of being coerced and avoid its negative effects. If many patients revised their belief on the need for and benefits of hospitalization during their stay, their perception of coercion was left partially unchanged.